Wave-absorbing material based on fly ash magnetic separation product and preparation method of wave-absorbing material
By reducing the hydrogen of the fly ash magnetic separation product, increasing the Fe3O4 content and introducing Fe, the problem of insufficient absorption performance of existing absorbent materials in the multi-frequency band is solved, and a wider effective absorption bandwidth and lower matching thickness are achieved.
Patent Information
- Application Number
- CN202510016003.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
AI Technical Summary
It is difficult for existing absorbent materials to have thin, wide, light and strong absorption properties at the same time, and the corresponding matching thickness is relatively large, which affects its effective absorption ability in multi-frequency bands.
By magnetic separation of fly ash, magnetic separation products are obtained and hydrogen reduction is performed under argon protection, and the reduction temperature and time are adjusted to increase the Fe3O4 content in the sample and introduce Fe, enhancing its complex dielectric constant and magnetic permeability.
It significantly improves the dielectric loss and magnetic loss of the sample, increases the effective absorption bandwidth, reduces the matching thickness, and has effective absorption capacity in multiple frequency bands (such as 4-5GHz, 8-9GHz, 11-13GHz, 16-18GHz).
Smart Images

Figure CN119833967A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of wave-absorbing materials, and in particular relates to a wave-absorbing material based on fly ash magnetic separation products and a preparation method thereof. Background Art
[0003] The rapid rise of the wireless technology industry has accelerated the development of whole-house intelligence and global intelligence. Similar to the environmental pollution caused by excessive accumulation of solid waste, excessive electromagnetic radiation and electromagnetic interference generated by smart life are also seriously threatening human health and safety. In order to avoid the threat of electromagnetic waves, cutting-edge academic workers have developed a series of absorbing materials. Ideal absorbing materials need the ability to absorb and dissipate EMW, including the influence of the internal structure and composition of the material. However, it is difficult for a single absorbing material to have the characteristics of thinness, width, lightness and strong absorption performance at the same time. Therefore, while ensuring that the material has strong absorption performance, increasing its effective absorption bandwidth and reducing its corresponding matching thickness have become research hotspots. As a material with complex components, it has many characteristics. Research on high-value-added functional materials made of fly ash as raw materials, especially EMW absorbing materials, has important social, economic and academic value.
[0004] Therefore, there is an urgent need to provide an absorbing material based on fly ash magnetic separation products and a preparation method thereof. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a wave absorbing material based on fly ash magnetic separation products and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a wave absorbing material based on fly ash magnetic separation products comprises the following steps:
[0009] magnetically separating the fly ash to obtain a magnetic separation product;
[0010] The magnetic separation product is heated to a target temperature under argon protection, then hydrogen reduced at this temperature, and then cooled to room temperature to obtain the wave absorbing material based on the fly ash magnetic separation product.
[0011] Furthermore, the magnetic separation process adopts a dry magnetic separation method.
[0012] Beneficial effects: The present invention reduces the magnetic separation product with hydrogen, and after introducing iron and increasing the content of ferroferric oxide in the sample, the dielectric loss and magnetic loss of the sample are significantly improved, and the complex magnetic permeability and complex dielectric constant of the sample are significantly improved. Among them, the introduction of iron causes the sample to have a double absorption peak on the reflection loss spectrum, which increases the effective absorption bandwidth of the sample, and the sample thickness corresponding to the optimal absorption peak intensity of the system sample is relatively low.
[0013] Optionally, the target temperature is 400°C-800°C; and the time for hydrogen reduction is 0.5h-3h.
[0014] Furthermore, the target temperature is 400°C, 500°C, 550°C, 600°C, 700°C and 800°C; and the time of hydrogen reduction is 0.5h, 1h, 2h and 3h.
[0015] Furthermore, the target temperature is 500° C.; and the time for hydrogen reduction is 2 hours.
[0016] Beneficial effects: The prepared samples of different thicknesses have effective absorption capabilities for electromagnetic waves in multiple frequency bands of 4-5GHz, 8-9GHz, 11-13GHz, and 16-18GHz. As the reduction temperature of the samples increases, the wave absorption performance of the samples shows a pattern of first getting better and then getting worse. This is because during the temperature increase, the Fe3O4 content in the samples first increases and then decreases, and the multiple loss mechanisms of Fe3O4 enhance the wave absorption performance of the samples. Similar to the temperature conditions, increasing the reduction time also shows a pattern of first getting better and then getting worse. Among them, the wave absorption performance of the sample reduced at 550℃ and 2h is the best, and the strongest reflection loss value is -43dB.
[0017] Optionally, the flow rate of hydrogen during the hydrogen reduction process is 20 sccm.
[0018] Optionally, the average content of iron oxide in the magnetic separation product is 54.765wt%.
[0019] The second technical solution of the present invention:
[0020] A wave absorbing material based on fly ash magnetic separation products is prepared by the above preparation method.
[0021] Optionally, the absorbing material has a strongest reflection loss value of -43dB at 14GHz, and the corresponding matching thickness is 3mm.
[0022] Beneficial effects: The present invention reduces the magnetic separation product with hydrogen, increases the content of Fe3O4 and introduces a certain proportion of Fe, thereby increasing the real part of the complex dielectric constant, reducing the imaginary part of the dielectric constant, reducing the real part of the complex magnetic permeability in the low-frequency band, and increasing the imaginary part of the magnetic permeability in the low-frequency band, thereby enabling the sample to obtain better wave absorbing performance.
[0023] Compared with the prior art, the present invention has the following advantages and technical effects:
[0024] The present invention successfully removes Fe2O3 from the magnetic separation product by hydrogen reduction of the magnetic separation product, and adjusts the reduction temperature and reduction time, thereby obtaining a product with a high ratio of Fe3O4 to Fe. The reduction temperature of 800°C and the reduction time of 2h are the optimal reduction conditions for converting Fe3O4 in the sample into Fe. The results of the electromagnetic parameters and reflection loss values of the wave absorption performance of the sample reduced by the magnetic separation product show that as the reduction temperature of the sample increases, the wave absorption performance of the sample shows a pattern of first getting better and then getting worse. This is because during the temperature increase process, the Fe3O4 content in the sample first increases and then decreases, and the multiple loss mechanisms of Fe3O4 enhance the wave absorption performance of the sample. Similar to the temperature conditions, the wave absorption performance of the sample also shows a pattern of first getting better and then getting worse as the reduction time increases. Among them, the wave absorption performance of the sample reduced at 550°C and 2h is the best. Under this condition, the sample has the best reflection loss value of -43dB near 14GHz, corresponding to a matching thickness of 3mm. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0026] Figure 1 This is a physical picture of the magnetic rod housing with a separation ring in the pull-out dry magnetic separation device of the present invention;
[0027] Figure 2 It is a schematic diagram of the working principle of the dry magnetic separation equipment of the present invention;
[0028] Figure 3 XRD patterns of samples at different reduction temperatures of the present invention;
[0029] Figure 4 The XRD patterns of the samples of the present invention at different reduction times of (a) 550° C. and (b) 800° C.;
[0030] Figure 5 This is a SEM image of a sample of a hydrogen reduction magnetic separation product of the present invention;
[0031] Figure 6 This is the XPS spectrum of Fe 2p of the sample reduced at 550°C for 1h in the present invention;
[0032] Figure 7 Magnetic hysteresis loops of the magnetic separation products of the present invention at different reduction temperatures;
[0033] Figure 8(a) dielectric real part (b) dielectric imaginary part (c) magnetic permeability real part (d) magnetic permeability imaginary part of the present invention at different Fe3O4 contents in 2-18GHz;
[0034] Fig. 9 The graphs of (a) dielectric loss tangent and (b) magnetic loss tangent of different Fe3O4 contents at 2 to 18 GHz of the present invention;
[0035] Fig.10 A three-dimensional surface diagram showing the variation of reflection loss values of samples with magnetic separation product contents of (a) 0%, (b) 20%, (c) 40%, (d) 60%, (e) 80% and (f) 100% at different thicknesses with frequency;
[0036] Fig.11 The quarter-wavelength theoretical matching thickness, reflection loss and normalized impedance matching curve of (a) magnetic separation product and (b) Fe3O4 of the present invention;
[0037] Fig.12 The (a) real part of dielectric (b) imaginary part of dielectric (c) real part of magnetic permeability (d) imaginary part of magnetic permeability of the magnetic separation product samples at different reduction temperatures of the present invention at 2 to 18 GHz;
[0038] Fig.13 The (a) dielectric loss tangent and (b) magnetic loss tangent spectra of the magnetic separation products of the present invention at different reduction temperatures at 2 to 18 GHz;
[0039] Fig.14 It is a three-dimensional surface diagram of the reflection loss value of the samples of the present invention (a) Fe3O4 pure sample, (b) 300℃, (c) 400℃, (d) 500℃, (e) 550℃, (f) 600℃, (g) 700℃ and (h) 800℃ at different thicknesses as a function of frequency;
[0040] Fig.15 The theoretical matching thickness, reflection loss and normalized impedance matching curve of the quarter-wavelength of the sample reduced at 600° C. for 1 h of the present invention;
[0041] Fig.16 It is the hysteresis loop of the magnetic separation product of the present invention at different reduction times at 550°C;
[0042] Fig.17 It is the hysteresis loop of the magnetic separation product of the present invention at different reduction times at 800°C;
[0043] Fig.18 The (a) real part of dielectricity, (b) imaginary part of dielectricity, (c) real part of magnetic permeability, and (d) imaginary part of magnetic permeability of the magnetic separation product of the present invention at 550°C and different reduction time at 2-18 GHz;
[0044] Fig.19 The (a) dielectric loss tangent and (b) magnetic loss tangent spectra of the magnetic separation products of the present invention at 550° C. and different reduction times at 2 to 18 GHz;
[0045] Fig. 20 The (a) real part of dielectric (b) imaginary part of dielectric (c) real part of magnetic permeability (d) imaginary part of magnetic permeability of the magnetic separation product of the present invention at 800°C and different reduction time at 2-18 GHz;
[0046] Fig.21 The (a) dielectric loss tangent and (b) magnetic loss tangent graphs of the magnetic separation products of the present invention at 800°C and different reduction times at 2 to 18 GHz;
[0047] Fig. 22 It is a three-dimensional surface diagram of the reflection loss value of the sample reduced at 550° C. (a) 0.5 h, (b) 1 h, (c) 2 h, and (d) 3 h at different thicknesses as a function of frequency;
[0048] Fig.23 The three-dimensional surface diagram of the reflection loss value of the sample reduced at 800°C (a) 0.5h, (b) 1h, (c) 2h, and (d) 3h according to the present invention at different thicknesses as a function of frequency;
[0049] Fig.24 The quarter-wavelength theoretical matching thickness, reflection loss and normalized impedance matching curves of the samples of the present invention (a) 550°C, 2h and (b) 800°C, 2h. DETAILED DESCRIPTION
[0050] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0051] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0052] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0053] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0054] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0055] The chemical composition and corresponding content (measured by XRF) of the fly ash used in the present invention are shown in Table 1 below.
[0056] Table 1 Chemical composition and corresponding content of fly ash
[0057]
[0058]
[0059] Example 1
[0060] A method for preparing a wave absorbing material based on fly ash magnetic products comprises the following steps:
[0061] (1) Magnetic separation of fly ash: Dry magnetic separation is used to separate fly ash. The specific operation is: the fly ash is slowly poured into the self-made dry magnetic separation equipment at a uniform speed for magnetic separation, and the product is collected at the discharge port, which is called the magnetic product. The gray-white powder obtained at the tailings port is the tailings.
[0062] The self-made dry magnetic separation equipment (reference patent CN 116328937 A) consists of a magnetic rod and a non-magnetic shell, on which 31 separation rings with a height of 3 mm and a width of 7 mm are arranged. Figure 1As shown. The separation ring is in a circular shape, and its function is to promote the relative movement of the magnetic and non-magnetic components in the entrained clusters to achieve effective separation. When the device is used for experiment, a quantitative sample (fly ash) is poured onto the separation ring of the device. The sample is magnetically separated by 31 separation rings to obtain a magnetic separation product. The product mass, the iron oxide content in the product, and the iron recovery rate are calculated. The specific working principle of magnetic separation is: at the beginning of magnetic separation, Figure 2 As shown in position A in the figure, fly ash enters the magnetic separation device from the feed port, and the magnetic particles are attracted by the magnetic rod and adsorbed on the surface of the magnetic rod. At the same time, after the magnetic particles are magnetized by the magnetic rod, they can be regarded as small magnets, which interact magnetically with each other to form dense clusters. When clusters are formed, non-magnetic particles are entrained by adjacent magnetic particles, are also mixed in the clusters, and are adsorbed on the surface of the magnetic rod. As the clusters move to the right with the magnetic rod, the magnetic particles continuously jump over the separation ring, and the non-magnetic particles in the clusters continuously fall off. When the magnetic rod is pulled to position C, the non-magnetic particles basically disappear, and the magnetic particles are blocked by the baffle on the port, and fall to the discharge port under the action of their own gravity, and finally complete the dry magnetic separation; the results of magnetic separation (two parallel tests) are shown in Table 2:
[0063] Table 2
[0064]
[0065] (2) Reduction of magnetic separation products: The magnetic separation products were placed in a TF55030A tubular furnace and heated to target temperatures of 400°C, 500°C, 550°C, 600°C, 700°C and 800°C under argon protection. Then, the products were reduced for 1 hour under a pure hydrogen atmosphere at a flow rate of 20 sccm. In order to explore the effect of the holding time on the magnetic separation products, two sintering temperatures of 550°C and 800°C were selected, and the reduction was performed under the conditions of 0.5h, 1h, 2h and 3h. The reduced products were cooled to room temperature in the furnace under argon protection.
[0066] Effect verification
[0067] 1. Structural morphology analysis
[0068] 1. Effect of reduction temperature on the degree of reduction of Fe3O4 in magnetic separation products
[0069] Figure 3The XRD diffraction patterns of the samples at a reduction temperature of 300℃ to 800℃ and a reduction time of 1h. The results show that when the reduction temperature is 400℃ or below, most of the Fe2O3 is reduced to Fe3O4; at 400℃, a weak α-Fe diffraction peak is observed at 57.059°, indicating that at this temperature, Fe3O4 has a tendency to transform into Fe; when the reduction temperature is increased to 550℃, the peak value of the α-Fe diffraction peak increases sharply, which is equivalent to the peak value of the Fe3O4 diffraction peak, indicating that at this temperature, a large amount of α-Fe appears; when the temperature rises to 600℃, the peak value of the α-Fe diffraction peak decreases, and the FeO diffraction peak appears, and Fe3O4 becomes This is because at above 580°C, the Fe3O4 phase is first reduced to the FeO phase and then transformed into the Fe phase; when the reduction temperature rises to 700°C, it is observed that the diffraction peak of α-Fe is much larger than the diffraction peak of Fe3O4, and there is no Fe2O3 diffraction peak at this time, indicating that most of the Fe3O4 in the sample is transformed into Fe, and only a small amount of Fe3O4 exists; when the temperature rises to 800°C, only diffraction peaks of α-Fe and SiO2 are observed, indicating that at this temperature, all the iron oxides in the sample have been transformed into elemental iron.
[0070] 2. Effect of reduction time on the degree of reduction of Fe3O4 in magnetic separation products
[0071] 550°C and 800°C were selected as the reduction temperatures of the samples, and the reduction time was changed in the range of 0.5h to 3h.
[0072] Figure 4 (a) is the XRD spectrum of the sample at a reduction temperature of 550℃ and a reduction time of 0.5h to 3h. The results show that with the increase of reduction time, the intensity of the Fe2O3 diffraction peak gradually weakens and disappears completely after 2h, indicating that there is no Fe2O3 phase in the sample after 2h of reduction; the intensity of the Fe3O4 diffraction peak increases first and then decreases, and the diffraction peak intensity of α-Fe gradually increases; the spectra of the 2h sample and the 3h sample are similar, indicating that at this temperature, the Fe3O4 in the sample cannot be completely reduced to Fe. Figure 4 (b) is the XRD spectrum of the sample with a reduction temperature of 800℃ and a reduction time of 0.5h to 3h. The results show that under the reduction conditions of 800℃ and 0.5h, there is still a weak Fe3O4 diffraction peak; when the reduction time is increased to 1h, there is no Fe3O4 diffraction peak, and no other phases are found when the reduction time is further increased.
[0073] 3. The morphology of the reduced samples was characterized by scanning electron microscopy
[0074] Figure 5The SEM image of the sample under 800℃, 1h reduction conditions. It can be seen from the figure that the morphology of the sample does not change much after reduction. Most of the sample particles are spherical, and the particle size difference between the particles is large. There are fine spherical particles attached to the particle surface.
[0075] Figure 6 This is the XPS spectrum of Fe 2p of the magnetic separation product sample under 550℃, 1h reduction conditions. It can be found from the figure that after calibration of the C1s peak of 284.8eV, the large peak at 712eV can be decomposed into four small peaks, namely: Fe single peak (711.15eV), Fe 2+ 2p 3 / 2 (712.3eV), Fe 3+ 2p 3 / 2 (714.1eV) and satellite peak (716.7eV); the peak at 726eV can be decomposed into Fe 2+ 2p 2 / 1 (723.41eV) and Fe 3+ 2p 2 / 1 (726.1eV). By calculating Fe, Fe 2+ , Fe 3+ Substitute the area of the peak of Fe elemental peak into the Fe elemental peak to obtain the Fe content in the sample. 2+ , Fe 3+ The total peak area is 23.01%, indicating that 23% of the iron element exists in the sample in the form of a single substance.
[0076] 2. Effect of reduction temperature on the performance of reduced samples
[0077] 1. To further study the effect of reduction time and reduction temperature on the magnetic properties of samples. The hysteresis loops of samples at different reduction temperatures are shown in Figure 1. Figure 7 As shown, the M of the reduced sample S 、M r and H C As shown in Table 3. Compared with the above XRD results, Figure 7 The results in Table 3 show that as the reduction temperature increases, the M S When the reduction temperature is 800℃, M S The reduction temperature of 300℃ has a slight effect on the reduction of the magnetic separation product, indicating that the reduction of part of the Fe2O3 in the magnetic separation product to Fe3O4 has a significant impact on the M content of the sample as a whole. S The effect is small; as the temperature increases, the M r and H C All of them showed a trend of increasing first and then decreasing, indicating that the increase of Fe3O4 content in the sample would make M r and HC Increase, while the increase of Fe content will make M r and H C Reduce.
[0078] Table 3 Magnetic properties of magnetic separation products at different reduction temperatures
[0079]
[0080] 2. In order to test the storage capacity of electromagnetic field energy and the attenuation capacity of electromagnetic waves of the samples after reduction of magnetic separation products, the coaxial line method was used to test the real part ε' and imaginary part ε" of the complex dielectric constant and the real part μ' and imaginary part μ" of the complex magnetic permeability of the reduced samples.
[0081] In order to explore the influence of Fe3O4 content in the sample on electromagnetic parameters, the present invention mixed the magnetic separation product and Fe3O4 sample at 0% to 100%, and the test results are as follows Figure 8 As shown. The results show that with the increase of Fe3O4 content, the real part of the dielectric constant increases from 5.9 to 6.6 (magnetic separation products) to 8.1 to 9.7 (Fe3O4) within 2 to 9 GHz; a strong dielectric relaxation peak of Fe3O4 samples is observed near 12 GHz, and the dielectric relaxation peak of samples with added magnetic separation products has an obvious backward shift trend, and the dielectric relaxation peak of 80% Fe3O4 samples is at 18+ GHz; with the increase of Fe3O4, μ' increases to a certain extent; within 2 to 4 GHz, all samples show a small amplitude magnetic resonance phenomenon, but this part of the resonance phenomenon is not regular.
[0082] Fig. 9 It reflects the tanδ of samples with different Fe3O4 contents at 2~18GHz μ and tanδ ε , which are obtained from μ' / μ" and ε" / ε', respectively, and characterize the loss capacity of the sample to electromagnetic waves. As can be seen from the figure, as the Fe3O4 content in the sample decreases, the dielectric loss tangent value of the sample decreases within 2-14GHz; the tanδ ε The maximum value is reached around 18 GHz, while the tanδ of pure Fe3O4 is ε The maximum value is reached around 12 GHz. ε The relationship between the change and the Fe3O4 content is not obvious, and it shows a gradual decrease trend in the range of 2 to 18 GHz. In the range of 2 to 8 GHz, the tanδ μ Greater than tanδ ε , indicating that the sample is mainly magnetic loss; at 8-18 GHz, the sample's tanδ μ Less than tanδ εAnd it decreases to below 0, indicating that the sample is mainly dielectric loss in this band. In addition, the tanδ ε Maximum value and tanδ μ The minimum values all move toward high frequencies, indicating that components such as SiO2 in the magnetic separation products will increase the sample's absorption capacity for high-frequency bands.
[0083] The above results show that appropriately increasing the content of Fe3O4 in the sample will increase the complex dielectric constant and complex magnetic permeability of the material, and the introduction of Fe will change the complex magnetic permeability of the material. In order to compare the wave absorption performance of each group of samples, it is necessary to calculate the reflection loss (RL) of the sample according to the transmission line theory, and the calculation formula is shown in 1:
[0084]
[0085] Where: RL represents the reflection loss of the sample; Z in It represents the input impedance when the medium is the sample; Z0 represents the impedance when the medium is air. in It can be obtained from formula 2:
[0086]
[0087] Where: Z in represents the input impedance when the medium is a sample; f represents the propagation frequency of the electromagnetic wave; d represents the thickness of the sample; c represents the speed of light; μ r Represents the complex magnetic permeability of the sample; ε r Indicates the complex dielectric constant of the sample. Generally speaking, if a material is to have an effective absorption capacity for electromagnetic wave energy, the material's absorption of electromagnetic waves must reach more than 90%. Then according to the formula, when the calculated RL value is lower than -10dB, the sample can be considered to have the ability to absorb electromagnetic waves in this band, and the corresponding frequency range is considered to be the effective absorption bandwidth, thereby judging the material's wave absorption performance.
[0088] Fig.10The three-dimensional surface diagram of the reflection loss value of the samples with different thicknesses of the magnetic separation product content of the present invention of (a) 0%, (b) 20%, (c) 40%, (d) 60%, (e) 80% and (f) 100% at different frequencies is obtained by calculation through formula (1) and formula (2). As shown in the figure, as the Fe3O4 content in the sample decreases, the maximum RL value of each sample shows a trend of first decreasing and then increasing, indicating that as the impurity content in the sample increases, the sample's absorption capacity of electromagnetic waves shows a law of first increasing and then decreasing. The effective absorption bandwidth of the pure Fe3O4 sample is about between 3GHz and 14GHz; when the thickness of the pure Fe3O4 sample is 5.5mm, it can effectively absorb electromagnetic waves in the 15GHz frequency band. When the content of magnetic separation products in the sample is 20%, the sample has the strongest absorption capacity for microwaves, and reaches the maximum value at the 15GHz frequency band, with a value of -29.57dB, and the thickness of the absorbent is 5.5mm at this time; in addition, another absorption peak of the sample is observed at the 17GHz frequency band, with a maximum RL value of -26.33dB; compared with the pure Fe3O4 sample, the effective absorption bandwidth of the sample after adding a small amount of impurities is significantly reduced. As the content of magnetic separation products in the sample increases, the maximum reflection loss value of the sample increases, the absorption capacity of electromagnetic waves decreases, and the frequency range of the effective absorption bandwidth decreases and moves to the high frequency range. This shows that after introducing an appropriate amount of impurities, the minimum value of the reflection loss of Fe3O4 can be reduced, that is, the absorption capacity of Fe3O4 in the 15GHz to 18GHz frequency band is enhanced, but at the same time the effective absorption frequency band of Fe3O4 for electromagnetic waves is reduced.
[0089] In the three-dimensional surface spectrum, almost all samples have double absorption peaks, which increases the effective absorption bandwidth of the material to a certain extent, making the material have diversified application capabilities and meet the needs of various working environments. The appearance of this double absorption peak can be explained by the quarter-wavelength interference theory, and its formula is:
[0090]
[0091] Where: d m is one quarter of the matching thickness of the sample; ε r is the complex dielectric constant of the sample; μ r is the complex magnetic permeability of the sample; f is the propagation frequency of electromagnetic waves; c is the speed of light; n is the matching thickness level (n = 1, 2, 3...). In addition, the normalized impedance matching Z can better evaluate the material's absorption performance of electromagnetic waves, and its formula is as follows:
[0092]
[0093] Where: Z inrepresents the input impedance when the medium is a sample; Z0 represents the impedance of free space; f represents the propagation frequency of electromagnetic waves; d represents the thickness of the sample; c represents the speed of light; μ r Represents the complex magnetic permeability of the sample; ε r Represents the complex dielectric constant of the sample. The closer the normalized impedance matching value is to 1, the less the electromagnetic wave is reflected into the free space after passing through the material, that is, the better the wave absorption performance of the material at this thickness. In order to illustrate the optimal thickness of the material and its impedance matching, the present invention combines and compares the curves of reflection loss, quarter matching thickness and normalized impedance matching and frequency change of the sample.
[0094] In formula (3), n=3, RL and d of magnetic separation product sample and Fe3O4 sample are m The spectrum of Z changing with frequency is as follows Fig.11 As shown. Fig.11 (a) It can be seen that the sample thickness at the absorption peak is 5.5 mm, which is consistent with the thickness matching of the other two mechanisms. At this frequency, the Z value of the 5.5 mm sample is close to 1. Fig.11 In Figures (a) and (b), the Fe3O4 sample shows an effective absorption bandwidth at all thicknesses, and the optimal sample thickness is also 5.5 mm. The absorption peaks at other thicknesses and the corresponding Z values are all greater than 1, indicating that the impedance matching theory can well explain the differences in the electromagnetic wave absorption ability of materials at different thicknesses.
[0095] 3. After studying the relationship between the proportion of magnetic separation products and the absorption performance, the present invention studies the relationship between temperature change and electromagnetic properties and absorption performance. The real and imaginary parts of the dielectric constant and the real and imaginary parts of the magnetic permeability of the samples obtained at different reduction temperatures are as follows: Fig.12 As shown. The results show that the electromagnetic absorption performance of the sample reduced at 300℃ and the magnetic separation product sample is slightly different; when the reduction temperature rises to above 400℃, the dielectric loss of the sample increases first and then decreases with the increase of the reduction temperature, and ε" also shows this law, indicating that the increase of the dielectric loss of the sample will enhance the microwave absorption capacity of the sample; in the 2-5GHz band, ε" is negative and a trough appears, indicating that the electric field energy cannot be stored in this band after the introduction of the iron phase; in the 2-5GHz band, the real part of the negative magnetic permeability of the sample decreases with the increase of the reduction temperature, indicating that it decreases with the increase of the content of Fe3O4 and Fe phase in the sample; after 5GHz, as the reduction temperature increases, the real part of the negative magnetic permeability of the sample increases, and a peak appears at 6.8GHz, with a peak value of 7.8; in the range of 2-6GHz, the μ" of the sample increases with the increase of the Fe content, and reaches a maximum value of 55 at 2GHz, indicating that the absorption of microwaves by the sample in this band is dominated by magnetic loss.
[0096] Fig.13is the magnetic loss tangent and dielectric loss tangent of the magnetic separation product at different reduction temperatures. From the figure, we can see that the tanδ of the 300℃ sample ε and tanδ μ Similar to the magnetic separation samples, this is because only a small amount of Fe2O3 is converted to Fe3O4 at the reduction temperature of 300℃. ε As the reduction temperature increases, it decreases significantly in the range of 0 to 10 GHz, but approaches that of the magnetic separation sample in the range of 10 to 18 GHz. μ There are extremely fluctuating peaks and valleys in the range of 2 to 4 GHz. This is caused by the fact that μ' of the reduced sample changes from negative to positive in the range of 2 to 4 GHz, and μ" has a very large value in the range of 2 to 4 GHz.
[0097] Fig.14 This is a three-dimensional surface diagram of the reflection loss of pure Fe3O4 samples and magnetic separation product samples treated at different reduction temperatures at different thicknesses. It can be seen from the figure that the three-dimensional surface diagram of the 300℃ reduced sample is close to the three-dimensional surface diagram of the pure Fe3O4 sample; when the sample thickness is 5.5mm, two RL minima appear in the low frequency band of 6GHz and the high frequency band of 17GHz, with a value of about -29dB; at this temperature, the effective absorption bandwidth of the sample is reduced and moves toward high frequency compared with the pure Fe3O4 sample. When the temperature rises to 400℃ and above, the Fe phase that appears in the sample greatly changes the three-dimensional curve of the sample, and the sample's absorption frequency band of electromagnetic waves is greatly narrowed. At multiple specific frequencies, the sample shows good absorption performance for electromagnetic waves. As the reduction temperature increases, the effective electromagnetic wave absorption frequency band of the sample moves toward high frequency; the sample reduced at 400℃ has good electromagnetic wave absorption performance in the 11GHz and 14GHz bands; the sample reduced at 500℃ and 550℃ has good electromagnetic wave absorption performance in the 7GHz, 8GHz, 12GHz and 13GHz bands; the sample reduced at 600℃ and 700℃ has good electromagnetic wave absorption performance in the 4GHz, 5GHz, 8GHz and 17GHz bands; the sample reduced at 800℃ has good electromagnetic wave absorption performance in the 8GHz and 13GHz bands. It shows that as the Fe content in the sample increases, the sample's absorption capacity for high-frequency electromagnetic waves increases. As the Fe content in the sample increases, the minimum value of the sample RL increases first and then decreases. The 700℃ sample is the best. Under the conditions of 2.5mm sample thickness and 17GHz, the minimum RL value is -38.58dB. As mentioned earlier, too high Fe content will lead to a decrease in the complex dielectric of the sample, affecting the absorption of electromagnetic field energy. In addition, the present invention also found that the introduction of the Fe phase reduces the optimal thickness of the sample for electromagnetic wave absorption, and the higher the Fe content, the thinner the thickness.
[0098] In order to show the impedance matching and quarter-wavelength theoretical matching of the samples with the best absorbing ability after treatment at different reduction temperatures, samples under the reduction conditions of 600℃ and 1h were selected, and n=9 was selected. The quarter-wavelength theoretical matching thickness, reflection loss and normalized impedance matching curves are shown in Figure 2. Fig.15 As shown. At this time, the matching degree of the optimal thickness is 9, the sample thickness is 5.5mm, and the corresponding impedance matching Z value is close to 1; when the sample is 5mm, the second strongest absorption peak is observed at high frequency, which is weaker than the absorption peak of 5.5mm. According to the impedance matching theory, the Z value is about 0.78, and it is inferred that the optimal thickness of the sample at high frequency is between 5mm and 5.5mm. The matching thickness level of thinner samples is lower. When n=3, the thickness of 2mm matches the quarter-wavelength theoretical model, and there is an effective absorption bandwidth in the low frequency band. The Z value is close to 1, which is consistent with the impedance matching theory.
[0099] 3. Effect of reduction time on sample performance
[0100] Fig.16 It is the hysteresis loop of the sample at 550℃ reduction temperature and 0.5h~3h reduction time. Their M S 、M r and H C As shown in Table 4. The results show that with the increase of reduction time, the M S The XRD patterns between 2h and 3h are similar, but the reduction time increases. S Increase, 0.5h, 1h, 2h, 3h reduction sample M S The M of the reduced samples were 48.61emu / g, 52.57emu / g, 58.74emu / g, and 66.72emu / g, respectively, indicating that more Fe3O4 was reduced to Fe; r and H C are better than the magnetic separation products, and with the increase of reduction time, the M r and H C It increases gradually, indicating that the content of Fe3O4 in the 3h reduced sample is higher than that in the 1h reduced sample.
[0101] Table 4 Magnetic properties of magnetic separation products at 550℃ with different reduction times
[0102]
[0103] Fig.17 is the hysteresis loop of the sample at 800℃ reduction temperature and 0.5h~3h reduction time. Their M S 、M r and H C As shown in Table 5. The analysis results show that with the increase of reduction time, the MS Increase; M of samples with 2h reduction time and 3h reduction time S The difference is not big. Comparing the XRD results, it shows that after 2h reduction, the iron oxide in the sample has been completely converted into iron. As the reduction time increases, the hysteresis loop of the sample becomes narrower. This is because the Fe content in the sample increases, resulting in M r and H C This indicates that 800℃ reduction temperature and 2h reduction time are the optimal process for reducing the magnetic separation product to Fe phase.
[0104] Table 5 Magnetic properties of magnetic separation products at different reduction times at 800℃
[0105]
[0106]
[0107] In addition, the present invention found that the 550℃ sample deviated from the relevant law presented by the temperature change under the temperature change conditions, which may be caused by the special relative ratio between Fe3O4 and Fe in the sample. In order to further explore the influence of reduction time on the electromagnetic parameters of the 550℃ reduction temperature sample, the present invention tested the ε', ε", μ' and μ" of the reduced sample in the range of 0.5h to 3h. The test results are as follows Fig.18 As shown. According to the analysis of the figure, at a reduction temperature of 550℃, as the reduction time increases, the ε' of the sample increases, reaching a peak value of about 76 at 5.2GHz, indicating that the increase in the Fe content in the sample will increase the sample's ability to store electromagnetic field energy; the ε" of all reduced samples is complex at 2-5GHz, indicating that the attenuation ability of electromagnetic waves in this band is poor; the 2h reduced sample has a dielectric relaxation peak at 16GHz, with a peak value of about 11; for the remaining samples except the 2h sample, no significant decrease in ε" was found with the change of Fe content, and there was a dielectric relaxation peak near 17GHz. The peak of μ' is about 7 at 7 GHz. At 2-4 GHz, negative values of μ' are observed, and as the reduction time increases, the curve shifts upward in this band, indicating that the Fe content in the sample increases and μ' of the sample increases. At the operating frequency of 6-18 GHz, the introduction of too much Fe phase will reduce the sample's ability to store electromagnetic waves, and the performance of the sample reduced for 1 h is the best. At 7 GHz, μ' peaks with a peak value of about 7. At 2-6 GHz, μ" of the sample is extremely large, indicating that the attenuation ability to microwaves is extremely strong. At 6-18 GHz, μ" of the sample tends to 0, and the attenuation ability to microwaves is weak.
[0108] Fig.19The results in the figure show that in the 2-6 GHz frequency band, as the reduction time increases, the dielectric loss tangent of the sample first increases and then decreases, but it is still negative, indicating that the sample has no dielectric loss capacity for electromagnetic waves in this band; the dielectric loss peak of the 2h reduction treatment appears near the 16GHz frequency, and is significantly higher than the other samples, indicating that the 2h reduction sample has the strongest electromagnetic wave loss capacity. Fig.19 Similar to (b), the magnetic loss tangent of the time-varying restored sample also shows obvious peak and valley values, indicating that the sample's loss capacity for electromagnetic waves varies significantly in the 2-4 GHz frequency band. When both the magnetic loss tangent and the dielectric loss tangent are negative, the sample will show an enhancement effect on electromagnetic waves rather than an absorption effect.
[0109] In order to explore the storage and attenuation capabilities of electromagnetic wave energy with Fe as the main absorber in the sample, the present invention tested the complex dielectric constant and complex magnetic permeability of the sample at a reduction temperature of 800°C and a reduction time range of 0.5 to 3 h. Fig. 20 The complex dielectric constant and complex magnetic permeability of samples at 800℃ with different reduction times at 2-18GHz. The results show that with the increase of reduction time, the storage capacity of the samples for electromagnetic field energy increases first and then decreases. The ε' peak of all samples is near 5GHz, indicating that the system samples have a high efficiency in microwave energy storage in the 5GHz band; there is a weak dielectric relaxation peak at 12-18GHz, and the ε" of the 2h sample performs best in this band; a peak of the μ' value appears at 7GHz, and the 1h reduction sample is the strongest, about 7.5, indicating that too high Fe content will reduce the material's storage performance for microwaves; the intensity of μ" is observed to obtain the material's ability to attenuate electromagnetic waves. The μ" value decreases with the extension of the reduction time, indicating that the material's attenuation ability has deteriorated.
[0110] Fig.21 The magnetic loss tangent and dielectric loss tangent spectra of the magnetic separation products at 800℃ and different reduction time conditions. As can be seen from the figure, the tanδ ε The law of change over time is not obvious, among which the tanδ of the 3h sample ε The lowest, tanδ of the sample at high frequencies ε The change from negative to positive indicates that the dielectric properties of the sample have loss capacity for high-frequency electromagnetic waves. This is because as the reduction time increases, more Fe3O4 is converted into Fe, which reduces the dielectric properties of the sample. Fig.21 (b) It can be seen that tanδ μThere are extremely different peak and valley values in the 2-4 GHz frequency band, and the extreme value increases with the restoration time, and is negative in the initial band. This shows that the sample does not have the ability to lose electromagnetic waves in the low frequency band, which will lead to the poor absorption performance of the sample in the low frequency band.
[0111] Substituting the complex magnetic permeability and complex dielectric constant of the sample with a preparation process of 550℃ reduction temperature and 0.5-3h reduction time into equation (1) and equation (2), the reflection loss of the sample at different thicknesses varies with frequency as shown in Fig. 22 As shown. It can be seen from the figure that all samples show strong absorption ability for electromagnetic waves in the medium and high frequency bands of 8GHz, 10GHz and 14GHz. Under the conditions of a reduction time of 0.5h and an operating frequency band of 14GHz, the reflection loss value of the sample is the best, about -36dB. When the reduction time increases to 1h, the reflection loss value of the sample weakens and the effective absorption bandwidth decreases. The reflection loss value of the 2h sample performs best, reaching -43dB in the 14GHz frequency band, and the absorption performance of microwaves is greatly improved. Increasing the reduction time to 3h, the reflection loss value of the sample decreases slightly, but the effective absorption bandwidth of electromagnetic waves increases, and it has good absorption ability for electromagnetic waves in both low and high frequency bands. Comparing the XRD spectra, magnetic permeability and dielectric constant of the samples, it is shown that the increase in iron content increases the real part of the dielectric constant of the sample in the low and high frequency bands, so that the sample exhibits excellent microwave absorption ability in the low and high frequency bands.
[0112] In order to study the effect of higher Fe content on the electromagnetic wave absorption performance of the sample, the three-dimensional surface diagram of the reflection loss value of the sample under the reduction conditions of 800℃ and 0.5h~3h with the change of frequency is shown in Figure 23. It can be found from the figure that the sample with a reduction time of 0.5h shows a good absorption capacity for microwaves at 6~10GHz and 18GHz; after increasing the reduction time to 1h, the optimal reflection loss value of the sample is not much different, but the effective absorption bandwidth moves to low frequency; after the reduction time continues to increase to 2h, the RL optimal value of the sample becomes better, reaching -39dB at 12GHz, and the overall absorption capacity of electromagnetic waves is greatly improved compared with the 0.5h and 1h reduction samples; although the 3h sample still has an effective absorption bandwidth for electromagnetic waves with frequencies of 12GHz and 14GHz, its absorption performance is significantly reduced compared with the 2h sample. Combined with the XRD spectrum of the sample, the poor performance of the 3h sample may be due to the fact that most of the sample is Fe and the Fe3O4 content is very small, which leads to a significant decrease in the values of ε' and μ' of the sample, thereby affecting the sample's absorption capacity for electromagnetic waves.
[0113] The samples reduced at 550℃ for 2h and 800℃ for 2h were selected to explore the influence of iron content on the matching thickness and impedance matching of the samples. Fig.24The following are the quarter-wavelength theoretical matching thickness, reflection loss, and normalized impedance matching curves of the two samples. When n=6, the two samples have a good matching degree to the quarter-wavelength theoretical model, and the thickness of the sample with the best absorption peak intensity is significantly reduced compared with the previous article; the impedance matching Z value corresponding to the best absorption peak of the two samples is close to 1 after normalization.
[0114] In summary, the present invention prepares a reduced sample of a magnetic separation product by adjusting the reduction time and reduction temperature. A reduction temperature of 300°C can convert Fe2O3 into Fe3O4. As the temperature increases, the conversion efficiency increases. Even at a reduction temperature of 400°C, a small amount of Fe3O4 in the magnetic separation product is converted into Fe. The higher the reduction temperature, the higher the proportion of Fe3O4 converted into Fe. At 800°C, most of the Fe3O4 is converted into Fe. By extending the reduction time, the proportion of Fe2O3 converted into Fe3O4 and Fe3O4 converted into Fe in the sample increases. When all the Fe3O4 in the sample is converted into Fe, the M of the sample is S The reduction temperature of 800℃ and the reduction time of 2h are the optimal reduction conditions for the conversion of Fe3O4 into Fe in the sample.
[0115] Mix the magnetic separation product with the pure Fe3O4 sample and change the ratio between the two. It is found that the Fe3O4 sample has a strong dielectric relaxation peak near 12GHz. As the proportion of the magnetic separation product in the sample increases, the dielectric relaxation peak moves to high frequency. The magnetic separation product sample has poor performance in quarter-wavelength model and impedance matching, resulting in its wave absorption performance being inferior to that of the pure Fe3O4 sample. After increasing the content of Fe3O4 in the magnetic separation product sample and introducing a certain proportion of Fe, the present invention can increase the real part of the complex dielectric constant, reduce the imaginary part of the dielectric constant, reduce the real part of the complex magnetic permeability in the low-frequency band, and increase the imaginary part of the magnetic permeability in the low-frequency band, so that the sample obtains better wave absorption performance.
[0116] The prepared reduced samples of different thicknesses have effective absorption capabilities for electromagnetic waves in multiple frequency bands of 4-5GHz, 8-9GHz, 11-13GHz, and 16-18GHz. As the reduction temperature of the samples increases, the wave absorption performance of the samples shows a pattern of first getting better and then getting worse. This is because during the temperature increase, the Fe3O4 content in the samples first increases and then decreases, and the multiple loss mechanisms of Fe3O4 enhance the wave absorption performance of the samples. Similar to the temperature conditions, increasing the reduction time also shows a pattern of first getting better and then getting worse. Among them, the wave absorption performance of the sample reduced at 550℃ and 2h is the best, with the strongest reflection loss value of -43dB.
[0117] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a wave absorbing material based on fly ash magnetic separation products, characterized in that: The following steps are involved: The fly ash is magnetically separated to obtain a magnetic separation product; the magnetic separation product is heated to a target temperature under argon protection, then hydrogen reduced at this temperature, and then cooled to room temperature to obtain the absorbing material based on the fly ash magnetic separation product.
2. The method for preparing a wave absorbing material based on fly ash magnetic separation products according to claim 1, characterized in that: The target temperature is 400°C-800°C; the time of hydrogen reduction is 0.5h-3h.
3. The method for preparing a wave absorbing material based on fly ash magnetic separation products according to claim 2, characterized in that: The target temperature is 400° C., 500° C., 550° C., 600° C., 700° C. or 800° C.; and the hydrogen reduction time is 0.5 h, 1 h, 2 h or 3 h.
4. The method for preparing a wave absorbing material based on fly ash magnetic separation products according to claim 3, characterized in that: The target temperature is 500° C.; the time for hydrogen reduction is 2 h.
5. The method for preparing a wave absorbing material based on fly ash magnetic separation products according to claim 1, characterized in that: The flow rate of hydrogen during the hydrogen reduction process is 20 sccm.
6. The method for preparing a wave absorbing material based on fly ash magnetic separation products according to claim 1, characterized in that: The average content of iron oxide in the magnetic separation product is 54.765wt%.
7. A wave absorbing material based on fly ash magnetic separation products, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.
8. The microwave absorbing material based on fly ash magnetic separation product according to claim 7, characterized in that: The absorbing material has a strongest reflection loss value of -43dB at 14GHz, and the corresponding matching thickness is 3mm.